2010
DOI: 10.1523/jneurosci.0534-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Early Pharmacotherapy Restores Neurogenesis and Cognitive Performance in the Ts65Dn Mouse Model for Down Syndrome

Abstract: Down syndrome (DS) is a genetic pathology characterized by intellectual disability and brain hypotrophy. Widespread neurogenesis impairment characterizes the fetal and neonatal DS brain, strongly suggesting that this defect may be a major determinant of mental retardation. Our goal was to establish, in a mouse model for DS, whether early pharmacotherapy improves neurogenesis and cognitive behavior. Neonate Ts65Dn mice were treated from postnatal day (P) 3 to P15 with fluoxetine, an antidepressant that inhibits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
188
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(208 citation statements)
references
References 62 publications
19
188
0
1
Order By: Relevance
“…It was noted that in prenatal and newborn Ts65Dn mice neurogenesis was significantly reduced (Chakrabarti et al, 2007;Contestabile et al, 2007;Lorenzi & Reeves, 2006). At postnatal day 2 cell proliferation in Ts65Dn mice, assessed 2 hours after single injection of bromodeoxyuridine (BrdU) was significantly reduced (Contestabile et al, 2007); similar results were revealed at postnatal day 15 (Bianchi et al, 2010). However in young adult Ts65Dn mice the results are conflicting (Clark et al, 2006;Rueda et al, 2005).…”
Section: Neurogenesis In Mouse Models Of Dsmentioning
confidence: 77%
See 1 more Smart Citation
“…It was noted that in prenatal and newborn Ts65Dn mice neurogenesis was significantly reduced (Chakrabarti et al, 2007;Contestabile et al, 2007;Lorenzi & Reeves, 2006). At postnatal day 2 cell proliferation in Ts65Dn mice, assessed 2 hours after single injection of bromodeoxyuridine (BrdU) was significantly reduced (Contestabile et al, 2007); similar results were revealed at postnatal day 15 (Bianchi et al, 2010). However in young adult Ts65Dn mice the results are conflicting (Clark et al, 2006;Rueda et al, 2005).…”
Section: Neurogenesis In Mouse Models Of Dsmentioning
confidence: 77%
“…Taking to account that this subject is very important for the neurobiology of DS, only a few papers addressed neurogenesis in mouse models of DS (Bianchi et al, 2010;Chakrabarti et al, 2007;Clark et al, 2006;Contestabile et al, 2007;Lorenzi & Reeves, 2006;Rueda et al, 2005). It was noted that in prenatal and newborn Ts65Dn mice neurogenesis was significantly reduced (Chakrabarti et al, 2007;Contestabile et al, 2007;Lorenzi & Reeves, 2006).…”
Section: Neurogenesis In Mouse Models Of Dsmentioning
confidence: 99%
“…After about 4 months, the neurons exhibit enlarged dendrites, but these dendrites stop growing within the first year, and the neurons then appear atrophied compared with neurons in a typical brain at the same age [7]. The expression levels of various neurotrophic factors, including brain-derived neurotrophic factor (BDNF), fall during early development of the brain of patients with DS [10]. BDNF is a neurotrophin that plays a key role in neurogenesis and the maintenance of neuronal plasticity by binding specifically to tropomyosin-related kinase receptor B [11].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely believed that neurogenesis enables hippocampal plasticity and new memories (Denis-Donini et al, 2008). In addition to neuronal apoptosis, several recent studies correlate alterations in neurogenesis with cognitive performance (Zhao et al, 2008;Bianchi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%